Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This paper examines the inflation expectations, monetary policy credibility, and dollarization. Country fundamentals have explained variation in sovereign spreads, but external factors play an important role. This paper assesses the role of and prospects for bank-lending from a cyclical and structural perspectives. A model calibrated for Uruguay, a financially dollarized economy, suggests that reserves are nearing optimal prudential levels. The results of a modified Merton framework, applied to the case of the Uruguayan banking system, appear to be promising for countries without equity markets.